Development Of Logical Thinking Of Future Teachers Of Mathematics Using The Methods Of Newton And Chebishev (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
This article is devoted to the methodology of developing logical thinking of future mathematics teachers using the methods of Newton and Chebyshev, based on a related approach. Effective methods for developing logical competencies of future mathematics teachers are described